2018
DOI: 10.1136/lupus-2017-000241
|View full text |Cite
|
Sign up to set email alerts
|

Very delayed lupus nephritis: a report of three cases and literature review

Abstract: Lupus nephritis (LN) affects up to 50% of patients with Systemic Lupus Erythematosus (SLE) and is associated with a worse prognosis. LN usually develops within the first 5 years of the onset of the disease. We report three patients with very delayed LN (DLN) diagnosed after 15 or more years after SLE diagnosis. The three patients were non-Caucasian women with adolescent or adult-onset SLE. Each had antinuclear, anti-dsDNA and anti-Ro antibodies. Hydroxychloroquine was prescribed for each. Their disease courses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The results of this study showed that lupus nephritis affected more than 60% of patients at the time of SLE diagnosis; however, a substantial number of patients developed lupus nephritis after SLE was diagnosed. In this study, the median disease duration of SLE in the delayed lupus nephritis group was < 5 years, which is consistent with data of previous studies [ 8 ]. Regarding the clinical characteristics, when lupus nephritis developed early in the course of SLE, affected patients were more likely to have higher disease activity and prominent multiple organ involvement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study showed that lupus nephritis affected more than 60% of patients at the time of SLE diagnosis; however, a substantial number of patients developed lupus nephritis after SLE was diagnosed. In this study, the median disease duration of SLE in the delayed lupus nephritis group was < 5 years, which is consistent with data of previous studies [ 8 ]. Regarding the clinical characteristics, when lupus nephritis developed early in the course of SLE, affected patients were more likely to have higher disease activity and prominent multiple organ involvement.…”
Section: Discussionsupporting
confidence: 93%
“…In general, lupus nephritis primarily occurs at the time of or within the first year of SLE diagnosis [ 7 ]. On the contrary, the frequency of lupus nephritis occurrence gradually decreases with time; the onset of lupus nephritis is reported to be uncommon after 5 years from SLE diagnosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lupus nephritis is a common and serious complication in patients with systemic lupus erythematosus (SLE), developing in almost 50% of cases of SLE [ 1 , 2 ]. In the majority of patients, LN develops within 5 years of diagnosis of SLE [ 3 ].…”
Section: Introductionmentioning
confidence: 99%